High temperature effect on the spores of Equisetum arvense L. - Kedves Miklós; Tóth Anita; Farkas Eszter (1991)
Freshly collected spores of Equisetum arvense L. were examined by light microscopy after different exposures time of high temperature at 200 °C. Qualitative changes observed as follows: Elaters partially or completely separate from the spores. Perispore also folds out from the exospore. These changes and the alterations in maximum spore size are represented in diagrams. No difference is found between the quantitative changes at 200 °C with time, even after 300 hours.
Keywords: Természettudományok; Biológiai tudományok